2021
DOI: 10.31234/osf.io/pgxn9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ventral prefrontal serotonin 1A receptor binding: a neural marker of vulnerability for mood disorder and suicidal behavior?

Abstract: BACKGROUND: Mood disorders and suicidality have moderate heritability and are associated with altered corticolimbic serotonin 1A receptor (5-HT1A) binding potential. However, it is unclear whether these alterations reflect heritable risk or resilience markers, compensatory mechanisms, or illness-related changes as 5-HT1A binding has never been reported in unaffected high risk individuals (HR) who have passed through the age of greatest risk for psychopathology onset. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…While studies using [ 11 C]-WAY100635 have consistently found depressed vs. HV differences in raphe nuclei 5-HT 1A R [34,36,87], the [ 11 C]CUMI-101-measured difference in 5-HT 1A R binding here seems to be limited to the hippocampus. Two recent analyses with [ 11 C]-CUMI-101 found differences in 5-HT 1A R binding potential between BD and HV groups in the raphe nuclei and across a large set of ROIs that included the hippocampus [37] and between a mixed-mood disorder sample at high-risk for mood disorder comprising https://doi.org/10.1192/j.eurpsy.2023.4 Published online by Cambridge University Press participants with MDD, BD, dysthymia and depressive disorder not otherwise specified and HVs in the ventromedial prefrontal cortex and the medial orbitofrontal cortex [88]. However, in Ananth et al 2020, there were no differences between BD and HV groups in the raphe nuclei or in a large set of ROIs [44].…”
Section: Discussionmentioning
confidence: 99%
“…While studies using [ 11 C]-WAY100635 have consistently found depressed vs. HV differences in raphe nuclei 5-HT 1A R [34,36,87], the [ 11 C]CUMI-101-measured difference in 5-HT 1A R binding here seems to be limited to the hippocampus. Two recent analyses with [ 11 C]-CUMI-101 found differences in 5-HT 1A R binding potential between BD and HV groups in the raphe nuclei and across a large set of ROIs that included the hippocampus [37] and between a mixed-mood disorder sample at high-risk for mood disorder comprising https://doi.org/10.1192/j.eurpsy.2023.4 Published online by Cambridge University Press participants with MDD, BD, dysthymia and depressive disorder not otherwise specified and HVs in the ventromedial prefrontal cortex and the medial orbitofrontal cortex [88]. However, in Ananth et al 2020, there were no differences between BD and HV groups in the raphe nuclei or in a large set of ROIs [44].…”
Section: Discussionmentioning
confidence: 99%